Distinct regulatory programs establish widespread sex-specific alternative splicing in Drosophila melanogaster. - Hartmann, B.; Castelo, R.; Miñana, B.; Peden, E.; Blanchette, M.; Rio, D.C.; Singh, R.; Valcárcel, J. (RNA (New York, N.Y.), 2011)
In Drosophila melanogaster, female-specific expression of Sex-lethal (SXL) and Transformer (TRA) proteins controls sex-specific alternative splicing and/or translation of a handful of regulatory genes responsible for sexual differentiation and behavior. Recent findings in 2009 by Telonis-Scott et al. document widespread sex-biased alternative splicing in fruitflies, including instances of tissue-restricted sex-specific splicing. Here we report results arguing that some of these novel sex-specific splicing events are regulated by mechanisms distinct from those established by female-specific expression of SXL and TRA. Bioinformatic analysis of SXL/TRA binding sites, experimental analysis of sex-specific splicing in S2 and Kc cells lines and of the effects of SXL knockdown in Kc cells indicate that SXL-dependent and SXL-independent regulatory mechanisms coexist within the same cell. Additional determinants of sex-specific splicing can be provided by sex-specific differences in the expression of RNA binding proteins, including Hrp40/Squid. We report that sex-specific alternative splicing of the gene hrp40/squid leads to sex-specific differences in the levels of this hnRNP protein. The significant overlap between sex-regulated alternative splicing changes and those induced by knockdown of hrp40/squid and the presence of related sequence motifs enriched near subsets of Hrp40/Squid-regulated and sex-regulated splice sites indicate that this protein contributes to sex-specific splicing regulation. A significant fraction of sex-specific splicing differences are absent in germline-less tudor mutant flies. Intriguingly, these include alternative splicing events that are differentially spliced in tissues distant from the germline. Collectively, our results reveal that distinct genetic programs control widespread sex-specific splicing in Drosophila melanogaster.